Biomechanics of the rabbit knee and ankle: Muscle, ligament, and joint contact force predictions - Grover, Dustin M.; Chen, Andrew A.; Hazelwood, Scott J. (Journal of biomechanics, 2007)
Mathematical models of small animals that predict in vivo forces acting on the lower extremities are critical for studies of musculoskeletal biomechanics and diseases. Rabbits are advantageous in this regard because they remodel their cortical bone similar to humans. Here, we enhance a recent mathematical model of the rabbit knee joint to include the loading behavior of individual muscles, ligaments, and joint contact at the knee and ankle during the stance phase of hopping. Geometric data from the hindlimbs of three adult New Zealand white rabbits, combined with previously reported intersegmental forces and moments, were used as inputs to the model. Muscle, ligament, and joint contact forces were computed using optimization techniques assuming that muscle endurance is maximized and ligament strain energy resists tibial shear force along an inclined plateau. Peak forces developed by the quadriceps and gastrocnemius muscle groups and by compressive knee contact were within the range of theoretical and in vivo predictions. Although a minimal force was carried by the anterior cruciate and medial collateral ligaments, force patterns in the posterior cruciate ligament were consistent with in vivo tibial displacement patterns during hopping in rabbits. Overall, our predictions compare favorably with theoretical estimates and in vivo measurements in rabbits, and enhance previous models by providing individual muscle, ligament, and joint contact information to predict in vivo forces acting on the lower extremities in rabbits.